2018
DOI: 10.1111/iji.12407
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin10 gene promoter polymorphisms (rs1800896, rs1800871 and rs1800872) and haplotypes are associated with the activity of systemic lupus erythematosus and IL10 levels in an Iranian population

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with unknown aetiology. According to the role of interleukin 10 (IL10) in SLE pathogenesis, the genetic alterations in its promoter region could be associated with elevated IL10 levels and exacerbated disease. Here, we investigated the association of genotype and haplotype frequencies of three IL10 gene promoter polymorphisms with susceptibility to SLE, IL10 plasma levels and disease activity of patients in an Iranian population. A total of 116… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
1
21
1
1
Order By: Relevance
“…6 A recent study showed that the CGT haplotype in the order of −592, −1082 and −819 had a significantly higher frequency in the patient group than in controls in Iranian studies. 13 Also, they noted the frequency of CGC haplotype was higher in patients with a higher SLEDAI score. Schotte et al.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…6 A recent study showed that the CGT haplotype in the order of −592, −1082 and −819 had a significantly higher frequency in the patient group than in controls in Iranian studies. 13 Also, they noted the frequency of CGC haplotype was higher in patients with a higher SLEDAI score. Schotte et al.…”
Section: Resultsmentioning
confidence: 98%
“…12 Several association studies have been conducted with IL-10 and SLE. 13,14 Based on the studies, it is observed that the promoter polymorphisms in the IL-10 gene are related to genetic susceptibility to SLE. 15 SNPs in both distal (3575 T/A, −2849 G/A, −2763 C/A) and proximal regions (−1082 A/G, −819 T/C, −592 C/A) have been reported to influence disease susceptibility among different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a research is done in Iran. This research forecast the connotation of promoter polymorphism of gene Interleukin 10 along with the action of SLE [12]. There are certain susceptible genes which trigger the SLE.…”
Section: Introductionmentioning
confidence: 89%
“…There were IL-10 plasma up regulations in CC and AA genotype carriers of -592 and -1082, respectively. The CC and TT genotype carriers at − 592 and − 819 regions respectively had also increased SLEDAI score [47]. Disturbed immune tolerance and T/B lymphocytes activation results in production of autoantibodies.…”
Section: Cytokinesmentioning
confidence: 99%